Desenvolvimento de um Teste Intradérmico de Hipersensibilidade com antígenos secretados de Corynebacterium pseudotuberculosis para o diagnóstico subclínico da Linfadenite Caseosa em pequenos ruminantes - Camila Azevedo Antunes de Oliveira (2011)
Corynebacterium pseudotuberculosis is a bacterium that can cause Caseous Lymphadenitis (CLA) in small ruminants and consequently reduce the productivity of infected animals. The disease is characterized by the formation of abscesses in superficial lymph nodes and / or internal organs. Several diagnostic methods for the subclinical form of CLA have been developed, but none of them with satisfactory efficiency and practicability. Thus, a standardized Intradermal Hypersensitivity Test (IHT) with proteins secreted by C. pseudotuberculosis for the diagnosis of subclinical CLA in small ruminants was developed in this study. The animals used in experiments were evaluated by clinical examination and laboratory assays and separated into two groups consisting of 10 positive goats (group A) and 10 negative goats (group B) for CLA. In parallel, proteins secreted from the bacterial strain MIC6 of C. pseudotuberculosis were extracted using the technique of three-phase partitioning (TPP) and quantified by the method of Bradford. Subsequently, the IHT has been standardized and applied intradermally at a dose of 0.1 mL in the left cervical region in a shaved area. In order to control the experiment it was applied 0.1 mL of Tris-HCl (pH 7.4) without the secreted proteins in the right cervical region in the same animals. The measurements of the IHT were performed with a Hauptner® cutimeter before inoculation and every 24 hours in six days. Group A showed the overall mean of the values of HIT on all days studied, significantly higher than in Group B. In the first 24 hours there was a peak of reaction, most obviously in group A, declining until 72h, tending to normality after 96 hours of application of HIT. All controls maintained their similar values in both groups during all days of evaluation. The standardized IHT for subclinical CLA diagnosis in goats showed promising results and will be improved for use in the control of the CLA